2020
DOI: 10.1177/0883073820909046
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Neck or Shoulder Pain Following Sport-Related Concussion Negatively Influences Recovery

Abstract: Our objective was to examine the effect of current neck or shoulder pain on concussion outcomes. Variables included symptom resolution and return-to-sport time, symptom severity, amount of school missed, and sleep disturbances. Three hundred twelve patients (37% female; median age = 15.0 years; evaluated median = 9 days postinjury) reported experiencing current neck or shoulder pain at initial evaluation, and 268 did not (31% female; median age = 14.7 years; evaluated median = 8 days postinjury). Neck or shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 33 publications
0
26
2
Order By: Relevance
“…In this sample of children presenting to a level 1 trauma center pediatric ED, 13.8% of the patients diagnosed with concussion reported neck pain. Although this prevalence estimate is less than reported for children seen during follow-up visits, [5][6][7] the findings demonstrate that a substantial minority of the pediatric concussion patients may have comorbid neck injury. As comorbid neck pain can signal a need for distinct personalized clinical management strategies, the findings imply that it would be valuable for emergency medicine providers to routinely screen for neck pain.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…In this sample of children presenting to a level 1 trauma center pediatric ED, 13.8% of the patients diagnosed with concussion reported neck pain. Although this prevalence estimate is less than reported for children seen during follow-up visits, [5][6][7] the findings demonstrate that a substantial minority of the pediatric concussion patients may have comorbid neck injury. As comorbid neck pain can signal a need for distinct personalized clinical management strategies, the findings imply that it would be valuable for emergency medicine providers to routinely screen for neck pain.…”
Section: Discussioncontrasting
confidence: 59%
“…6 A study of sports-related concussion found that patients with concurrent neck and shoulder pain were more likely to have delayed recovery in comparison with those without concurrent neck and shoulder pain. 7 Because many ED patients are likely not to receive follow-up after discharge, it would be valuable to establish how often neck pain is identified in the ED setting itself. Furthermore, better understanding of injury or personal factors that predict neck pain and the impact of neck pain on the number follow-up visits may inform clinical care of pediatric patients with mTBI as these symptoms may need to be addressed by targeted therapy as has been suggested in previous position statements on concussion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with previous research that reported individuals who manifested with neck pain following a concussion had more severe and longerlasting symptoms. 11 Several previously identified risk factors, such as sex and mechanism of injury, have been identified such that female subjects were previously reported to be more likely to report comorbid neck pain and car accidents are the mechanism associated with the greatest risk of comorbid neck pain. 21 Similarly, in the present study, adolescent female athletes were twice as likely to report acute neck pain.…”
Section: Discussionmentioning
confidence: 99%
“…13 The prevalence of neck pain following a concussion has been reported to range from 7% to 68% in the acute stages 10,[20][21][22] and increase up to 90% in individuals suffering from PPCS. 11,12,23,24 In addition to delayed recovery, neck pain at time of injury has been reported to contribute to more severe overall postconcussion symptoms and postconcussion sleep disturbances. 11 Importantly, all previous studies exploring the prevalence of neck pain following a concussion have used data from emergency rooms or specialty clinics, which represent only a small subset of concussion cases that are often beyond acute phase (,24-48 hours) of recovery and heterogeneous mechanisms or injuries [ie automobile accidents, playground falls, trauma with a blunt object, sportsrelated concussion (SRC)].…”
Section: Introductionmentioning
confidence: 99%